Aplikasi Programable Logic Control (PLC) Pada Penerangan Jalan Umum yang Hemat Energi - Jefri Lianda; Johny Custer (UIN Sultan Syarif Kasim Riau, 2015)
Based on the strategic issues of the development of rock and hill districts Siak Kecil as Industrial Zone, Port and Agribusiness demand developments, improvements and fixtures public roads. Road equipment that is needed is a street lighting (PJU). PJU condition mounted in the district of Bukit Batu and Siak Kecil using AC lamps with high wattage power thus increasing the burden of payment of electricity accounts PJU. This study makes setting brightness lamp LED 60 watts using Programble Logic Control (PLC). Adjust the brightness level control (Illumenation) based on time. Hours 1830WIB - 2200 WIB illumenasi used 100% and hours 2200 WIB - 0600 WIB illumenation only 70%., Then to electrical energy efficiency but does not reduce the comfort of road users, forming an industrial area that is energy efficient.Keywords: illumination, LED, PLC